PENGENDALIAN PENYAKIT LAYU FUSARIUM TOMAT: APLIKASI ABU BAHAN ORGANIK DAN JAMUR ANTAGONIS CONTROL OF TOMATO FUSARIAL WILT: APPLICATION OF ORGANIC ASH AND ANTAGONISTIC FUNGI - Rahayuniati, Ruth Feti; Mugiastuti, Endang (Pembangunan Pedesaan, 2009)
The aims of this research were to determine the effect of organic ash and antagonistic fungi on controlling tomato Fusarium wilt. Factorial Completely Randomized Design has been used in hisresearch. There were paddy husk and legume ash as organic ash factor, and T. harzianum and Gvirensasantagonistic fungi factor. The result showed that combination of antagonistic fungi (Tharzianum and G. virens) and organic ash (paddy husk and legume ash) could suppress the disease growth, incubation period, disease severity, and disease rate. The effectiveness of the combination were about 36.79-43.30%.